Temporomandibular joint dysfunction in various rheumatic diseases - F.J. Aceves-Avila; M. Chávez-López; J.R. Chavira-González; C. Ramos-Remus (PAGEPress Publications, 2013)
Temporomandibular disorder (TMD) is an inclusive term in which those conditions disturbing the masticatory function are embraced. It has been estimated that 33% of the population have signs of TMD, but less than 5% of the population will require treatment. The objective of this study was to measure the frequency of TMD in rheumatoid arthritis (RA), osteoarthrosis (OA), ankylosing spondylitis (AS) and systemic lupus erythematosus, and to define the limitations in everyday's life that patients perceive when present. A six-month survey of consecutive outpatients in a rheumatology clinic in a teaching hospital in Mexico was carried out. We defined TMD as: 1) the presence of pain; 2) difficulty on mouth opening, chewing or speaking; 3) the presence of non-harmonic movements of the temporomaxilar joints. All three characteristics had to be present. Z test was used to define differences between proportions. We present the results of 171 patients. Overall, 50 patients had TMD according to our operational definition (29.24%). Up to 76% of the sample had symptoms associated with the condition. TMD is more frequent in OA and in AS (29.24% vs 38% OA, P=0.009; 39% AS; P=0.005). We found no association between the severity of TMD and the request for specific attention for the discomfort produced by the condition. Only 8 of 50 (16%) patients with TMD had requested medical help for their symptoms, and they were not the most severe cases. TMD is more frequent in RA and OA. Although it may produce severe impairment, patients seem to adapt easily.